New exact solutions of the (3+1)-dimensional double sine-Gordon equation by two analytical methods - Manzoor, Zuha; Iqbal, Muhammad Sajid; Ashraf, Farrah; Alroobaea, Roobaea; Tarar, Muhammad Akhtar; İnç, Mustafa; Hussain, Shabbir (Springer, 2024)
The (3+1)-dimensional double sine-Gordon equation plays a crucial role in various physical phenomena, including nonlinear wave propagation, field theory, and condensed matter physics. However, obtaining exact solutions to this equation faces significant challenges. In this article, we successfully employ a modified (G'/G(2)) -expansion and improved tan (phi(xi)/2) methods to construct new analytical solutions to the double sine-Gordon equation. These solutions can be divided into four categories like trigonometric function solutions, hyperbolic function solutions, exponential solutions, and rational solutions. Our key findings include a rich spectrum of soliton solutions, encompassing bright, dark, singular, periodic, and mixed types, showcasing the (3+1)-dimensional double sine-Gordon equation ability to model diverse wave behaviors. We uncover previously unreported complex wave structures, revealing the potential for complex nonlinear interactions within the (3+1)-dimensional double sine-Gordon equation framework. We demonstrate the modified (G'/G(2)) -expansion and improved tan phi(xi)/2) -expansion methods effectiveness in handling higher-dimensional nonlinear partial differential equations, expanding their applicability in mathematical physics. These method offers enhanced flexibility and broader solution categories compared to conventional approaches.
Keywords: (3+1) -Dimensional double sine-Gordon equation; Solitons solutions; Modified (G'/G(2)) -expansion method; Improved tan phi(xi)/2) -expansion method